Polymer-assisted self-assembly of gold nanoparticle monolayers and their dynamical switching - Ding, Tao (Royal Society of Chemistry, 2016)

(untitled) (Nanoscale)
Dynamic switching of plasmonic monolayers built of gold nanoparticles (AuNPs) is achieved using nano-coatings of poly(isopropyl acrylamide) (PNIPAM). The distance between AuNPs can be dynamically tuned through the repeatable expansion and contraction of the PNIPAM shells at different temperatures, which results in rapid switching of the optical properties of the AuNP monolayer.